Carbon Dioxide Quantification in Human Breath Using Infrared Thermography - Paes, Vitor Furtado; Rosa, Jucélia Nascimento; Porto, Matheus Pereira (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2026)
Carbon dioxide concentration in exhaled breath is a clinical metric for assessing respiratory and metabolic function. However, traditional capnography systems require physical contact, which can cause patient discomfort. This paper presents an exploratory investigation into the use of quantitative optical gas imaging as a non-invasive, remote sensing alternative for dynamically estimating CO 2 in human breath. A pilot study was conducted using a cooled mid-wave infrared thermographic camera and a narrow-bandpass filter. The results revealed peak CO 2 concentrations of approximately 50,000 ppm (5%) during nasal exhalation, consistent with standard physiological end-expiratory baseline ranges.